ISOLASI DAN IDENTIFIKASI SENYAWA ANTIFUNGAL AKAR Acacia mangium DAN AKTIVITASNYA TERHADAP Ganoderma lucidum - Nur Hidayati; SM Widyastuti; Subagus Wahyuono (Center for Forest Biotechnology and Tree Improvement (CFBTI), 2012)
Acacia mangium has been planted on large scale of industrial forest plantation in Indonesia, especially in Sumatera and Kalimantan islands. It has been reported that huge number of mangium plantations on those areas infected rot root disease caused by Ganoderma lucidum. To date, there was no information of mangium which resist to Ganoderma lucidum Moreover, research to get this information had been carried out with two aims as listed below: (1) isolate and identify a compound with antifungal properties from the roots of healthy mangium, and (2) identify the effect of the antifungal compound from roots of healthy mangium on Ganoderma lucidum The roots of healthy mangium from the first generation of seedling seed orchard in Wonogiri, Central Java, were used as material of this research. Mangium roots which had had their external and internal parts separated were macerated in a solvent of n-hexane and methanol. Methods of the isolation of the antifungal compound were the thinlayer chromatography (TLC), column chromatography and thin layer preparative chromatography. Antifungal effect test was carried out by using inhibition of germination and of hyphal growth of Fusarium sp. Ultraviolet (UV) spectrometry, Infrared (IR) and Gas Chromatography – Mass Spectrometry (GC-MS) were used to identify the antifungal compound. Antifungal effect test on Ganoderma lucidum was done with a modification of the cylinder plate method, performed in vitro.The results revealed that the antifungal compound succeed isolated in its Substance B form from methanol extract from the interior of the root. Substance B showed the highest level of antifungal activity through inhibiting germination and inhibiting of germination tube growth of Fusarium sp. This was shown by the highest percentage inhibiting of germination (66,67%), and the highest percentage inhibiting of germination tube (66,03%). The inhibition zone of hyphal growth of Ganoderma lucidum macroscopically from the antifungal compound was observed at a concentration of 1800 μg/ml. Microscopically, in the area of contact with the antifungal compound, hyphal curling and distorting of tips took place at a concentration of 1500 μg/ml one day after application of the antifungal compound. Based on the analysis of GC-MS spectra, the antifungal was identified as p-Methoxybenzylidene p aminophenol in the category of phenolic compounds.